Math, asked by Anmol11117, 1 year ago

factorise (x+y) (2x+3y)-(x+y) (x+1)

Answers

Answered by snehitha2
214
(x+y) (2x+3y)-(x+y) (x+1)

Factorization:-

= (x+y) (2x+3y)-(x+y) (x+1)

=(x+y)[2x+3y-(x+1)]

=(x+y)(2x+3y-x-1)

=(x+y)(x+3y-1)

Simplification:-

= (x+y) (2x+3y)-(x+y) (x+1)

=x(2x+3y)+y(2x+3y)-[x(x+1)+y(x+1)]

=2x²+3xy+2xy+3y²-[x²+x+xy+y]

=2x²+5xy+3y²-x²-x-xy-y

=x²+4xy+2y²-x-y

Hope it helps....
Answered by bhanupratapsingh51
91

Answer:

x+y(x+3y-1)

Step-by-step explanation:

(x+y)(x+3y)-(x+y)(x+1)

x+y(2x+3y-(x+1))

x+y(2x+3y-x-1)

x+y(2x-x+3y-1)

x+y(x+3y-1)

Similar questions